Nipping an education myth in the bud: Poh's brain activity during lectures. (August 2014) - Masters, Ken
Abstract: The debate around the value of lectures is raging strongly, and new empirical data arguing against the value of lectures comes from a chart showing student brain activity during lectures. The evidence from the chart, however, suffers from crucial problems. These include a small and unspecific sample, mislabeling of the student activities, and a misinterpretation of the type of measurement. This chart has appeared on the Internet, in education conferences and journals, and recently at a medical education conference. For medical education to be taken seriously, it is crucial that researchers apply the same standards that they would to clinical research. As a result, this chart should be avoided in the debate on the value of lectures before it has a chance to follow a pattern in medical education set by other myths.